2019
DOI: 10.1111/appy.12355
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the evidence regarding the use of telemedicine to deliver video‐interpreting during dementia assessments for older people

Abstract: Introduction As Australia's aging population increases and diversifies, there will be a growing need to address the burden of dementia among culturally and linguistically diverse (CALD) communities. Due to a lack of CALD‐appropriate services and bilingual health professionals, older people from CALD backgrounds often receive a delayed diagnosis of dementia. The use of telemedicine (TM) to deliver video‐interpreting services may overcome the barriers of interpreter availability when diagnosing and assessing dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…However, in accordance to our result, patient and physician satisfaction remained high even in patients with cognitive impairments like dementia, multiple sclerosis, or movement disorders. 4,13,[15][16][17] In our study, when the physician and the patient were asked if the teleconsultation replaced the physical consultation, they disagreed. This agreement had never been studied, several studies reported preference of the patients for face-toface consultation.…”
Section: Discussionmentioning
confidence: 74%
“…However, in accordance to our result, patient and physician satisfaction remained high even in patients with cognitive impairments like dementia, multiple sclerosis, or movement disorders. 4,13,[15][16][17] In our study, when the physician and the patient were asked if the teleconsultation replaced the physical consultation, they disagreed. This agreement had never been studied, several studies reported preference of the patients for face-toface consultation.…”
Section: Discussionmentioning
confidence: 74%
“…The potential benefits of TeleNP have long been recognised, including convenience, user satisfaction, potential cost-reductions and improved access (geographic; availability of interpreter services [ 46 ]). Nonetheless, the neuropsychological community has not uniformly embraced the adoption of TeleNP necessitated by the emergence of COVID-19.…”
Section: Practical Considerations For Telenpmentioning
confidence: 99%
“…The use of interpreters via telemedicine had overcome these barriers to care and was comparably feasible and acceptable to that of in-person interpretation. 34 When the psychiatrist and patient do not speak in a common language or dialect or have cultural differences, it can hamper their interaction, causing a gap in communication of the clinical management. In such a scenario, albeit interpreters are of great help, they skip communicating the nuances of patients’ intimate, sensitive details to psychiatrists.…”
Section: Dimensions Of Telepsychiatric Carementioning
confidence: 99%